Retinoids in development and disease - Ghyselinck, Norbert; Duester, Gregg (Current topics in developmental biology, 2025)
Retinoids in Development and Disease, Volume 161 in the Current Topics in Developmental Biology series focuses on the role of retinoids during development and disease. Topics covered include Retinoids, Retinol-Binding Protein 2 (RBP2), Retinol-Binding Protein 4 (RBP4): Obesity and Metabolic Disease, Early Retinoic Acid Signaling Organizes the Body Axis and Defines Domains for the Forelimb and Eye, Rethinking Retinoic Acid Self-Regulation: A Signaling Robustness Network Approach, Meiotic initiation in the fetal ovary without retinoic acid receptors: an unforeseen twist, Action of retinoic acid on progenitor cells in the testis, amongst many other topics. Additional sections cover Retinoic acid homeostasis and disease, Redefining the roles of endogenously produced retinoic acid in heart development and regeneration: lessons from genetic models, The Multifaceted Roles of Retinoids in Vision, Eye Development, and Retinal Degenerative Diseases, Essential roles for retinoid signaling in craniofacial development, and much more.